Study Of The Potential For Floating Solar Power Plant In Situ Gede Bogor City - Bilasi, Kris Stefan; Notosudjono, Didik; Rijadi, Bloko Budi (Journal of Energy and Electrical Engineering, 2024)
Floating Solar Power Plant utilized in research is located in Situ Gede Bogor City. The utilization of the situ area which has a land area of . With a power plant area utilization plan of 1 Hectare the potential average solar radiation at Situ Gede is . The total energy generated is . This research uses a Interactive Microgrid as a solar power system configuration scheme. The components used are Monocrystalline solar modules with a capacity of 500 Wp totaling 4200 units, 22 inverter units with a capacity of 2458 kW, a battery unit value the total capacity is 3634,634 kW with a total of 1818 battery units, and the battery inverter capacity of 25000 W, with a total battery inverter capacity value of 8034,78 kW, which is the total use of 3 battery inverter units. The simulation results on PVSyts obtained the value of solar power plant in one year is 3148720 kWh a Performance Ratio of 84.48% and a Capacity Factor value of 17.19%. With a total initial investment cost of Rp85.033.240.352, the Payback Period is obtained in a period of 11 years with an estimated operating time of 20 years.